Block Copolymer Directed Metamaterials and Metasurfaces for Novel Optical Devices. Issue 16 (13th May 2021) - Alvarez‐Fernandez, Alberto; Cummins, Cian; Saba, Matthias; Steiner, Ullrich; Fleury, Guillaume; Ponsinet, Virginie; Guldin, Stefan
Abstract: Optical metamaterials are artificially engineered architectures that exhibit desired optical properties not found in nature. Bespoke design requires the ability to define shape, size, orientation, and composition of material structures on the nanometer length scale. Bottom‐up self‐assembly methods, such as block copolymer (BCP) templating, offer unique pathways to tailored features, at spatial resolution not routinely achieved by conventional top‐down techniques. In this review, the authors provide the general readership with basic concepts of the underlying fabrication processes and examine optical phenomena arising from BCP‐derived metamaterials and nanoresonators, with both dielectric and plasmonic characteristics. A number of diverse structural conformations designed by BCP templating and their implementation in optical devices is evaluated. The discussion includes 3D metamaterials, such as gyroidal and hyperbolic arrangements, as well as 2D metasurfaces. Based on recent developments in exploring these emerging structural and material configurations, the review further highlights unexplored opportunities offered by BCP self‐assembly for novel metamaterials and metasurface devices. Abstract : Optical metamaterials constitute an emerging field, which has completely redefined how light is understood in many research areas. Block copolymer self‐assembly offers a straightforward, rapid and low‐cost fabrication strategy for new functional optical materials. This review article surveys the vast potential of block copolymer templating for dictating optical phenomena derived from metamaterial and metasurface designs.